2014
DOI: 10.1080/17461391.2014.905986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speed on local dynamic stability of locomotion under different task constraints in running

Abstract: A number of studies have investigated effects of speed on local dynamic stability of walking, although this relationship has been rarely investigated under changing task constraints, such as during forward and backward running. To rectify this gap in the literature, the aim of this study was to investigate the effect of running speed on local dynamic stability of forward and backward running on a treadmill. Fifteen healthy male participants took part in this study. Participants ran in forward and backward dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…This finding may indicate that although the control required for BW is different to FW, both have a similar response to increased speed. Previous findings in backward and forward running have found that dynamic stability decreases with increasing speed similarly in both directions (Mehdizadeh et al, 2014). During FW, activity of the prefrontal cortex is increased with increasing walking speed (Hamacher et al, 2015;Harada et al, 2009;Suzuki et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This finding may indicate that although the control required for BW is different to FW, both have a similar response to increased speed. Previous findings in backward and forward running have found that dynamic stability decreases with increasing speed similarly in both directions (Mehdizadeh et al, 2014). During FW, activity of the prefrontal cortex is increased with increasing walking speed (Hamacher et al, 2015;Harada et al, 2009;Suzuki et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
“…multiscale entropy (MSE), changes across the lifespan with the development of the gait pattern (Bisi and Stagni, 2016). Recent studies have demonstrated that BW has similar long-range autocorrelations of stride intervals compared to FW (Bollens et al, 2014), or greater long-range autocorrelations suggesting the stride interval is more predictable in BW than FW (Dierick et al, 2017), and that increasing speed decreases local dynamic stability of trunk motion of backwards running (Mehdizadeh et al, 2014). Non-linear analyses provide insight into the neural control dynamics of locomotion (Bruijn et al, 2009;Costa et al, 2003;Dierick et al, 2017;Dingwell and Cusumano, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kibushi et al (2018) revealed that LDS decreases while walking speed accelerates. Regarding the running performance, Mehdizadeh et al (2014) reported lower LDSs while the running speeds increase, either in forward or in the backward running. Besides, it has been highlighted that either increment or decrement of walking speed results in increased nonlinear variability in lower limb joint range of motion (Kang & Dingwell, 2008).…”
mentioning
confidence: 92%
“…All of these factors, and the fluctuation between them, influence the distribution of effort between the aerobic and anaerobic components, hampering the measurement of total energy consumption. However, the increase in speed promotes a reduction in body stability in a similar manner in both types of motor action, which explains the decrease of the difference in energy consumption with increasing intensity (speed) ( 28 ). In other words, with the increase in speed, and concomitant increased demand of the anaerobic system, there is a reduction in the consumption of oxygen.…”
Section: Discussionmentioning
confidence: 99%